Menegakkan Keadilan: Strategi Hukum dalam Menindak Penyelundupan Pakaian Bekas Impor - Jumadi Jumadi; Sunardi Purwanda; Anisah Daeng Tarring (Jurnal Litigasi Amsir, 2024)
This research is to determine the substance of the legal regulation regarding the smuggling of imported used clothes. The type of research used is normative research. Meanwhile, normative research uses a rational-theoretical model with deductive logical reasoning (drawing conclusions from general to specific). Normative legal research tends to image law as a prescriptive scientific discipline. The steps taken to tackle the smuggling of used clothes in Parepare City are carried out in a preventive and repressive manner. Preventative action is to prevent the smuggling of used clothing so that the circulation of used clothing on the market decreases. In contrast, repressive action is an action taken against the smuggling of used clothing that aims to prevent perpetrators from wanting it anymore and to prevent smuggling, mainly used clothing (paws).